Implementation of learning during the covid-19 in college - Eka Putri, Kharisma; Aditia Wiguna, Frans (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
The purpose of this study was to obtain information regarding the implementation of learning during the Covid-19 pandemic period in college. This research activity uses a type of library research which means that in obtaining data in the form of information on relevant matters from various sources such as documents, books, magazines, news, and others. The criteria for selected articles and news are those that discuss the implementation of learning during the Covid-19 pandemic in college. From the 10 sources obtained, then the most relevant were selected so that 7 articles were obtained. The results obtained in this study indicate that the implementation of learning during the Covid-19 pandemic in college can be carried out properly and effectively using online learning. Another finding is that the Covid-19 pandemic is a momentum for lecturers and students to start and familiarize online learning with various learning applications. And there are many online learning applications, but the applications that are widely used are the Google Classroom and Whatsapp applications